Combinatorial Pattern Matching 24th Annual Symposium, CPM 2013, Bad Herrenalb, Germany, June 17-19, 2013, Proceedings - Fischer, Johannes; Sanders, Peter (Theoretical Computer Science and General Issues, 2013)
This book constitutes the refereed proceedings of the 24th Annual Symposium on Combinatorial Pattern Matching, CPM 2013, held in Bad Herrenalb (near Karlsruhe), Germany, in June 2013. The 21 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 51 submissions. The papers address issues of searching and matching strings and more complicated patterns such as trees, regular expressions, graphs, point sets, and arrays. The goal is to derive non-trivial combinatorial properties of such structures and to exploit these properties in order to either achieve superior performance for the corresponding computational problem or pinpoint conditions under which searches cannot be performed efficiently. The meeting also deals with problems in computational biology, data compression and data mining, coding, information retrieval, natural language processing, and pattern recognition.